1991 Proceedings, International Conference on Wafer Scale Integration
DOI: 10.1109/icwsi.1991.151725
|View full text |Cite
|
Sign up to set email alerts
|

WSI interconnect issues: practical experience gained on the WASP project

Abstract: Internal interconnect and external interfacing are important elements of a WSI device. This paper examines these areas, with particular reference to the practical experience gained on the WASP project. A recent WASP technology demonstrator device is presented as a case study and measurements from actual devices are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…The trunk buses are formed on the HDI wafer and connect with the wafer interface blocks and data routers on the main wafer via indium bumps. The bus is the subject of current research, and is assumed here to incorporate the fault tolerant track selection scheme recommended in [13]. Each trunk bus segment is accessible via three of the six adjacent wafer interface blocks.…”
Section: A Hypothetical Wasp Devicementioning
confidence: 99%
See 3 more Smart Citations
“…The trunk buses are formed on the HDI wafer and connect with the wafer interface blocks and data routers on the main wafer via indium bumps. The bus is the subject of current research, and is assumed here to incorporate the fault tolerant track selection scheme recommended in [13]. Each trunk bus segment is accessible via three of the six adjacent wafer interface blocks.…”
Section: A Hypothetical Wasp Devicementioning
confidence: 99%
“…Indeed, several authors [ 113, [ 121 have reported interconnect defect problems in practice. Furthermore, recent defect mapping experiments performed on a representative WSI device, WASP (WSI Associative String Processor [3]), have shown the occurrences of interconnect defects of varying sizes on WASP bus structures [13], [14]. Figs.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This paper was presented at the IEEE Intemational Conference on Wafer Scale Integration, San Francisco, CA, January 18- 20, 1995. M. Hussaini and R. Lea [3]), have shown the occurrences of interconnect defects of varying sizes on WASP bus structures [13], [14]. Figs.…”
mentioning
confidence: 96%